Star‐Shaped Ruthenium Complexes as Prototypes of Molecular Gears. Issue 71 (21st November 2019) - Erbland, Guillaume; Abid, Seifallah; Gisbert, Yohan; Saffon‐Merceron, Nathalie; Hashimoto, Yuichiro; Andreoni, Leonardo; Guérin, Théo; Kammerer, Claire; Rapenne, Gwénaël
Abstract: The design and synthesis of two families of molecular‐gear prototypes is reported, with the aim of assembling them into trains of gears on a surface and ultimately achieving controlled intermolecular gearing motion. These piano‐stool ruthenium complexes incorporate a hydrotris(indazolyl)borate moiety as tripodal rotation axle and a pentaarylcyclopentadienyl ligand as star‐shaped cogwheel, equipped with five teeth ranging from pseudo‐1D aryl groups to large planar 2D paddles. A divergent synthetic approach was followed, starting from a pentakis( p ‐bromophenyl)cyclopentadienyl ruthenium(II) complex as key precursor or from its iodinated counterpart, obtained by copper‐catalyzed aromatic Br/I exchange. Subsequent fivefold cross‐coupling reactions with various partners allowed high structural diversity to be reached and yielded molecular‐gear prototypes with aryl‐, carbazole‐, BODIPY‐ and porphyrin‐derived teeth of increasing size and length. Abstract : Geared up : Two families of molecular‐gear prototypes were designed and synthesized by a divergent approach, with the aim of achieving controlled intermolecular gearing on a surface. The seven star‐shaped ruthenium complexes incorporate a pentaarylcyclopentadienyl ligand as cogwheel, equipped with teeth ranging from pseudo‐1D biphenyl groups to planar carbazole‐, BODIPY‐, and porphyrin‐derived 2D paddles (see figure).